Human-centered engineering: the challenges of Nigerian engineer. Issue 2 (29th April 2014) - Ismaila, S.O.; Samuel, T.M.
Abstract : Purpose: – There is the need to focus on humans while designing engineering facilities for users. The need to focus on Nigerians when designing for them is presented in this paper. The paper aims to discuss these issues. Design/methodology/approach: – Relevant literatures were consulted on the history of ergonomics and its importance was stressed. Some instances where ergonomics should be applied in the country were identified. Findings: – The paper observed that the application of ergonomics in Nigeria is low and some constraints that are militating against the use of ergonomics in Nigeria are discussed. Originality/value: – The paper suggested ways to fully imbibe the use of human-centered engineering (ergonomics) in Nigeria.